(untitled) (Nativa, 2023)
The present study delves into the public perceptions concerning prototype rural landscapes in China, aiming to unravel respondents’ varied layers of appreciation, concerns, and aspirations. Employing a quantitative approach through a structured questionnaire, the survey collected insights from a diverse demographic to unveil compelling facets of rural landscape perceptions. The findings revealed a collective admiration for cultural heritage preservation, natural beauty, and traditional architectural styles within rural settings. However, amidst this appreciation, concerns regarding infrastructural deficiencies, environmental sustainability, and socio-economic disparities emerged. These insights underscore the necessity of integrating public perceptions into future landscape planning endeavors to develop culturally resonant, sustainable and community-centric rural landscapes. Recommendations for future research highlight avenues for deeper exploration, emphasizing the need for innovative strategies to bridge infrastructural gaps, enhance environmental sustainability, and empower communities in shaping the future of rural landscapes in China. Keywords: prototype rural landscapes; public perception; landscape design; community development. Explorando as percepções públicas dos protótipos de paisagens rurais na China contemporânea: um estudo baseado em pesquisas RESUMO: O presente estudo investiga as percepções do público sobre os protótipos de paisagens rurais na China, com o objetivo de desvendar as diversas camadas de apreciação, preocupações e aspirações dos entrevistados. Empregando uma abordagem quantitativa, através de um questionário estruturado, recolheu-SE informações de um grupo demográfico diversificado para revelar facetas convincentes das percepções daS paisagens rurais. As descobertas revelaram uma admiração coletiva pela preservação do património cultural, pela beleza natural e pelos estilos arquitetônicos tradicionais em ambientes rurais. No entanto, no meio desta apreciação, surgiram preocupações relativas às deficiências infra-estruturais, à sustentabilidade ambiental e às disparidades socioeconômicas. Estas percepções sublinham a necessidade de integrar as percepções do público nos futuros esforços de planeamento paisagístico para desenvolver paisagens rurais culturalmente ressonantes, sustentáveis e centradas na comunidade. As recomendações para pesquisas futuras destacam caminhos para uma exploração mais profunda, enfatizando a necessidade de estratégias inovadoras para colmatar lacunas infra-estruturais, melhorar a sustentabilidade ambiental e capacitar as comunidades na definição do futuro das paisagens rurais na China. Palavras-chave: protótipo de paisagens rurais; percepção pública; projeto paisagístico; desenvolvimento comunitário.